Pure small fiber neuropathy in alcohol dependency detected by skin biopsy - Kokotis, Panagiotis; Papantoniou, Michail; Schmelz, Martin; Buntziouka, Chrysanthi; Tzavellas, Elias; Paparrigopoulos, Thomas (Alcohol, 2023)
Background - Alcohol overconsumption is well known to cause damage to the peripheral nervous system. The aim of this study was the functional and structural evaluation of the small nerve fibers in alcohol-dependent subjects, with or without symptoms of peripheral neuropathy. - Methods - Twenty-six consecutive alcohol-dependent subjects treated for detoxification voluntarily in the specialized unit of the Athens University Psychiatric Clinic were enrolled in this prospective study over 18 months. Every subject was assessed by peripheral nerve evaluation using the Neuropathy Symptoms Score (NSS) and Neuropathy Impairment Score (NIS), followed by nerve conduction studies (NCS), quantitative sensory testing (QST), and skin biopsy. Twenty-nine normal subjects, age- and gender-matched, constituted the control group. - Results - Peripheral neuropathy was diagnosed in 16 subjects (61.5%). Among these 16 subjects, pure large fiber neuropathy (LFN) was found in two subjects (12.5%), pure small fiber neuropathy (SFN) was found in eight subjects (50%), and both large and small fiber neuropathy was diagnosed in six patients (37.5%). The intraepidermal nerve fiber density (IENFD) of the patients’ skin biopsy was significantly lower than that of the control group. Additionally, QST results showed a statistically significant sensory impairment in the patients. - Conclusions - Our study confirms small fiber neuropathy due to alcohol abuse with a high prevalence of pure SFN that might have remained undetected without QST and IENFD.